P108 SLEEP DISORDERS IN INFLAMMATORY BOWEL DISEASE: THE FORGOTTEN DISCUSSION. (18th January 2018) - Almedimigh, Abdulaziz; Szeto, Stephanie; Dave, Jenny; Alsulaimi, Najwan; Myint, Aung; Borum, Marie L
Abstract: The relationship between sleep disturbances and inflammatory conditions is incompletely understood. Studies have shown that inflammatory bowel disease (IBD) patients have poorer sleep quality, prolonged sleep latency and increased use of sleeping pills compared to controls. Furthermore, patients with clinically active IBD have reported significantly worse sleep than patients with inactive disease. IBD patients in remission with abnormal sleep, may be at increased risk for relapse. This study evaluated physicians' assessment of sleep patterns in IBD patients. A medical record review of consecutive IBD patients seen at a university gastroenterology practice during a 6 month period was performed. Patient age, gender and disease type (Crohn's disease, ulcerative colitis) were obtained. Records were reviewed for documentation of a sleep assessment, sleep disorder or a formal sleep evaluation. A database was created maintaining patient confidentiality. The study was approved by the university IRB. 268 records (118 men, 150 women; mean age 43; 158 Crohn's, 109 ulcerative colitis (UC), 1 indeterminate colitis) were reviewed. Eleven patients (4.1%; 7 Crohn's, 4 UC) had a documented sleep disorder; 6 with obstructive sleep apnea, 2 insomnia, 1 circadian rhythm disorder, 1 with snoring. No other patients had documentation of a sleep discussion or assessment. There was no significant difference the rate of sleep assessment based upon gender, age or disease type (p=1.000). Sleep disorders may have an impact upon clinical outcomes in IBD patients. All IBD patients should be screened and treated for sleep disorders if appropriate. This study reveals that few IBD patients have documented discussions with their gastroenterologists about sleep patterns. While this study is limited due to size and single institutional design, it demonstrates a need for increased sleep evaluation in IBD patients, since early intervention for sleep disorders may improve clinical outcomes.